A functionalist approach to online trolling - Nitschinsk, Lewis; Tobin, Stephanie J.; Vanman, Eric J. (Frontiers in Psychology, 2023)
Online trolling is often linked to sadism and psychopathy. Yet, little research has assessed why people high in these traits seek online environments to achieve their nefarious goals. We employ a functionalist approach to examine whether people high in sadism and psychopathy are motivated to seek the affordances of online environments (e.g., anonymity) to reveal their malevolent self-aspects by engaging in trolling behavior. A sample of 515 university undergraduates (Mage = 20.47) read vignettes depicting trolling incidents and rated the acceptability of the perpetrators' actions and whether they had ever written similar comments.Participants then completed measures of psychopathy, sadism, and toxic anonymous motivations. We find that toxic anonymous motivations partially mediate the relationship between psychopathy and sadism, and online trolling. Whereas trolling is often understood through its underlying personality traits, toxic motivations to seek anonymity may be a more proximal predictor of who is likely to troll online.